CompTIA Network+ guide to networks - West, Jill (Author of CompTIA Network+ guide to networks); Dean, Tamara; Andrews, Jean, 1946-; Cengage Learning (Firm) (Australia : Cengage, 2019)
Master the technical skills and industry knowledge you need to begin an exciting career installing, configuring and troubleshooting computer networks with West/Dean/Andrews' NETWORK+ GUIDE TO NETWORKS, 8th edition. It thoroughly prepares you for success on CompTIA's Network+ N10-007 certification exam with fully mapped coverage of all objectives, including protocols, topologies, hardware, network design, security and troubleshooting. Virtualization-based projects give you experience working with a wide variety of hardware, software, operating systems and device interactions, while "On the Job" stories, Applying Concepts activities, and Hands-On and Capstone Projects let you explore concepts in more depth. MindTap Networking offers additional practice and certification prep. The text's emphasis on real-world problem solving provides the tools for success in any computing environment -- Publisher.
Introduction to networking -- Network infrastructure and documentation -- Addressing on networks -- Network protocols and routing -- Network cabling -- Wireless networking -- Virtualization and cloud computing -- Subnets and VLANs -- Network risk management -- Security in network design -- Network performance and recovery -- Wide Area Networks -- Appendix A. CompTIA Network+ N10-007 certification exam objectives -- Appendix B. Visual guide to connectors -- Appendix C. CompTIA Network+ practice exam.
Earlier editions are published as: Network+ guide to networks / Tamara Dean.
Registered trademark symbol appears after CompTIA in title.
Includes index.
000-099
Keywords: Computer networks -- Examinations -- Study guides; Telecommunications engineers -- Certification -- Study guides; Computer networks -- Examinations; Telecommunications engineers -- Certification; Study guides; Study guides